(untitled) (AYUSHDHARA, 2025)
Addiction is a chronic, complex, and multifaceted condition affecting millions globally. Characterized by the compulsive use of substances or engagement in harmful behaviors despite adverse consequences. Addiction requires a comprehensive, individualized approach addressing physical, emotional, and psychological dimensions. This article explores the Ayurvedic perspective on de-addiction, detailing traditional therapeutic strategies-detoxification, rejuvenation, psychological interventions, herbomineral formulations, and dietary recommendations-and outlines the regulatory framework that ensures the safe and effective use of these Ayurvedic formulations.